A case report of bladder and intestinal endometriosis, and the relationship between sex hormone receptor expression and PIK3CA mutation analysis - Kanto, Akiko (BMC Womens Health, 2021)
BACKGROUND: Extragonadal endometriosis is a rare condition, and its disease manifestation and long-term prognosis have not been elucidated. We report an extragonadal endometriosis case controlled by drug therapy for 14 years with analysis of the sex hormone receptor expression and PIK3CA mutation. CASE PRESENTATION: The patient was diagnosed with bladder endometriosis at age of 30 years, and underwent bilateral nephrostomy and GnRHa therapy with add-back therapy. The patient was switched to dienogest therapy at age 35 and had hematuria and bloody stools at age 38. PET-CT revealed a 6-cm mass in the bladder with fluorodeoxyglucose accumulation and the diagnosis of endometriosis in the bladder, sigmoid colon, and cecum was confirmed after the biopsy result. The lesion’s tubular structures were positive for the estrogen receptor, but only 30% positive for the progesterone receptor, and the H1047R mutation in PIK3CA was found in tubular structures of the bladder lesion. GnRHa therapy caused the tumors to shrink. CONCLUSION: Decreased progesterone receptor expression and oncogenic mutations may influence the course of less common and rare site endometriosis. Rare site endometriosis often requires long-term hormone therapy, and management should be tailored to the patient's life stage, keeping in mind complications, such as decreased bone density.